High Spatial‐Resolution and Acquisition‐Efficiency Cardiac MR T1 Mapping Based on Radial bSSFP and a Low‐Rank Tensor Constraint - Gao, Juan; Gong, Yiwen; Emu, Yixin; Chen, Zhuo; Chen, Haiyang; Yang, Fan; Ding, Zekang; Hua, Sha; Jin, Wei; Hu, Chenxi (Journal of magnetic resonance imaging, 2025)
Background Cardiac T1 mapping is valuable for evaluating myocardial fibrosis, yet its resolution and acquisition efficiency are limited, potentially obscuring visualization of small pathologies. Purpose To develop a technique for high‐resolution cardiac T1 mapping with a less‐than‐100‐millisecond acquisition window based on radial MOdified Look‐Locker Inversion recovery (MOLLI) and a calibrationless space‐contrast‐coil locally low‐rank tensor (SCC‐LLRT) constrained reconstruction. Study Type Prospective. Subjects/Phantom Sixteen healthy subjects (age 25 ± 3 years, 44% females) and 12 patients with suspected cardiomyopathy (age 57 ± 15 years, 42% females), NiCl2‐agar phantom. Field Strength/Sequence 3‐T, standard MOLLI, radial MOLLI, inversion‐recovery spin‐echo, late gadolinium enhancement. Assessment SCC‐LLRT was compared to a conventional locally low‐rank (LLR) method through simulations using Normalized Root‐Mean‐Square Error (NRMSE) and Structural Similarity Index Measure (SSIM). Radial MOLLI was compared to standard MOLLI across phantom, healthy subjects, and patients. Three independent readers subjectively evaluated the quality of T1 maps using a 5‐point scale (5 = best). Statistical Tests Paired t‐test, Wilcoxon signed‐rank test, intraclass correlation coefficient analysis, linear regression, Bland–Altman analysis. P < 0.05 was considered statistically significant. Results In simulations, SCC‐LLRT demonstrated a significant improvement in NRMSE and SSIM compared to LLR. In phantom, both radial MOLLI and standard MOLLI provided consistent T1 estimates across different heart rates. In healthy subjects, radial MOLLI exhibited a significantly lower mean T1 (1115 ± 39 msec vs. 1155 ± 36 msec), similar T1 SD (74 ± 14 msec vs. 67 ± 23 msec, P = 0.20), and similar T1 reproducibility (28 ± 18 msec vs. 22 ± 15 msec, P = 0.34) compared to standard MOLLI. In patients, the proposed method significantly improved the sharpness of myocardial boundaries (4.50 ± 0.65 vs. 3.25 ± 0.43), the conspicuity of papillary muscles and fine structures (4.33 ± 0.74 vs. 3.33 ± 0.47), and artifacts (4.75 ± 0.43 vs. 3.83 ± 0.55). The reconstruction time for a single slice was 5.2 hours. Data Conclusion The proposed method enables high‐resolution cardiac T1 mapping with a short acquisition window and improved image quality. Evidence Level 1 Technical Efficacy Stage 1